Field performance of tractor mounted with various implements: a case study/ Nazura Amanda Zainal Abidin and Darius El Pebrian - Zainal Abidin, Nazura Amanda; El Pebrian, Darius (Faculty of Plantation and Agrotechnology, 2018)
Field data performance are important in farm management where the proper used of tractor and implements can minimize inputs and fully optimized the machinery. This study is to investigate the efficiency of the implements. The field performance was developed by using Kubota M8540tractor and various mounted implements. The performance measures effective field capacity ‘wheel slippage and time taken for the implements to complete the task. Three implements that used are disc plough, rotary tiller and seeder machine at constant engine speed 1500 rpm was examined. All the implements were investigated on 20m X 20m site. The studies were undergoing5 replications to minimize the error and increase the efficiency. Time taken was collected in minutes and wheel slippage was taken in percentage while field capacity is in hectare per hours. Analysis from ANOVA on wheel slippage shows that disc plough have highest wheel slippage compared to rotary tiller and seeder. Furthermore, time taken to complete the task., highest is rotary ‘tiller (26.6 min), then disc plough (23.7 min) and seeder (14.52 min). Effective field capacity that shows by seeder is the highest where it can covers 1.0106 hectares per hour compared to disc plough 0.3216 hectares per hours and rotary tiller 0.2353 hectares per hours. From the ranges in performance measured, seeder is the most efficient implement to be used with the tractor. In order to use the machine efficiently, the tractor and implements should be matching properly in size and capacity'.